2008
DOI: 10.3402/ijch.v67i5.18354
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of post-partum care among pregnant women living in the north of Sweden

Abstract: Objectives. To describe expectations of post-partum care among pregnant women living in the north of Sweden and whether personality determines preference for care systems. The time for post-partum care on maternity wards has been reduced in Western countries. This, along with the reduction in special medical treatments offered and the closure of small hospitals has affected pregnant women and their families. Study Design. Data was extracted from a questionnaire and a personality instrument (SSP) that were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…That study reported, however, on experiences with individual care. The results in the present study could also be discussed in light of the results of another previously published Swedish study that focused on mothers' perceptions of postpartum care; participants identified that one of the most important people in postpartum care was the father of the baby, rather than the midwife (Lindberg et al, 2008).…”
Section: The Group Is a Forum For Sharing Experiencesmentioning
confidence: 72%
“…That study reported, however, on experiences with individual care. The results in the present study could also be discussed in light of the results of another previously published Swedish study that focused on mothers' perceptions of postpartum care; participants identified that one of the most important people in postpartum care was the father of the baby, rather than the midwife (Lindberg et al, 2008).…”
Section: The Group Is a Forum For Sharing Experiencesmentioning
confidence: 72%
“…The support of the woman is based on the father's knowledge of her needs. His support is valuable for the woman and the well-being of the new family (Lindberg et al, 2008;Premberg et al, in press). …”
Section: Feeling Self-confidentmentioning
confidence: 96%
“…First-time mothers have expectations about continued contact with the maternity ward staff, i.e. a home visit and telephone contact (Lindberg et al, 2008). A home visit by a midwife is not a standard practice in maternity care in Norway, even though women are discharged from the hospital only a few days after the birth.…”
Section: Feeling Self-confidentmentioning
confidence: 99%
“…There has been little research to assess the experience of quality and satisfaction with the considerably altered postpartum hospital care during the last 20 years 6,10–13 . In searching the PubMed database with different combinations of the keywords “maternity ward,”“satisfaction,”“postpartum,” and “hospitalization,” we found 9 relevant studies addressing the postpartum stay in maternity wards and exploring the quality of the care and mothers’ satisfaction, either as national or regional surveys or related to single hospital maternity wards 6,10 , 12–18 . Among these studies, only 1 was from the United States 16 .…”
Section: Research On Postpartum Carementioning
confidence: 99%
“…6,[10][11][12][13] In searching the PubMed database with different combinations of the keywords "maternity ward," "satisfaction," "postpartum," and "hospitalization," we found 9 relevant studies addressing the postpartum stay in maternity wards and exploring the quality of the care and mothers' satisfaction, either as national or regional surveys or related to single hospital maternity wards. 6,10,[12][13][14][15][16][17][18] Among these studies, only 1 was from the United States. 16 The national surveys that address the quality of postpartum hospital care are mainly from Australia or Sweden.…”
Section: Research On Postpartum Carementioning
confidence: 99%